Waveguide sub‐wavelength structures: a review of principles and applications. Issue 1 (30th September 2014) - Halir, Robert; Bock, Przemek J.; Cheben, Pavel; Ortega‐Moñux, Alejandro; Alonso‐Ramos, Carlos; Schmid, Jens H.; Lapointe, Jean; Xu, Dan‐Xia; Wangüemert‐Pérez, J. Gonzalo; Molina‐Fernández, Íñigo; Janz, Siegfried
<x xml:space="preserve">Abstract</x> With the recent development of silicon photonics and high resolution lithography, periodic structures with a sub‐wavelength pitch have found widespread application. This review provides an introduction to the physics of sub‐wavelength structures and an extensive overview of their applications in waveguide devices, including: high efficiency fiber‐chip couplers, wavelength multiplexers, athermal waveguide and ultra‐broadband waveguide couplers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>